Graphene protection improves the stability of two‐dimensional halide perovskites under the electron irradiation. Issue 11 (26th July 2022) - Yuan, Biao; Hua, Ziyi; Jia, Shunhan; Lu, Yuan; Shi, Enzheng; Yu, Yi
Abstract: The crystal structure of two‐dimensional (2D) organic–inorganic halide perovskites undergoes fast structural collapse under the electron beam irradiation, hindering high‐resolution transmission electron microscopy imaging. Graphene protection is an effective solution to mitigate the damage of electron‐beam irradiation and has been applied in 2D materials such as MoS2 . However, the effectivity of graphene protection has not been demonstrated in 2D halide perovskites yet, as traditional wet‐transfer of graphene with aqueous solution would cause serious degradation for moisture‐sensitive halide perovskites. Here, we verified that graphene protection plays a protection role and developed a method using nonpolar solvent to transfer the graphene layer atop the perovskite nanosheets. With this method, the perovskite nanosheets might be well protected by graphene encapsulation. Highlights: Transfer method of graphene on moisture‐sensitive 2D halide perovskites using nonpolar solvents was developed. Graphene substrate is proven to be able to mitigate electron‐beam damage to 2D halide perovskites. Encapsulation structure of graphene/halide perovskite/graphene was demonstrated. Abstract : The schematic diagrams and procedures for transfering single‐layer graphene (left) and the second‐layer graphene (right).